2007
DOI: 10.1111/j.1572-0241.2006.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Intestinal Metaplasia in the Esophagus and Esophagogastric Junction: Incidence and Clinical Data

Abstract: (a) Normalization of SIM occurs most frequently in EGJSIM>SSBE>LSBE. (b) Factors associated with normalization favor less severe GER and shorter segments of SIM. (c) Surveillance of LSBE results in the greatest yield for identifying dysplasia and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 63 publications
1
32
2
Order By: Relevance
“…These data appear to support the previous contention that patients with longer BE are at higher risk of developing EAC [80]. Horwhat et al [18] also showed that the incidence density for EAC/dysplasia in an LSBE cohort was 7.7 % pyrs, whereas the incidence density of dysplasia was 1.8 % pyrs in the SSBE cohort. In contrast, another meta-analysis by Yousef et al [64] found no difference in the pooled estimate of overall cancer incidence between patients with LSBE (0.67 % pyrs) and those with SSBE (0.61 % pyrs).…”
Section: Be Length and Carcinogenesissupporting
confidence: 79%
See 1 more Smart Citation
“…These data appear to support the previous contention that patients with longer BE are at higher risk of developing EAC [80]. Horwhat et al [18] also showed that the incidence density for EAC/dysplasia in an LSBE cohort was 7.7 % pyrs, whereas the incidence density of dysplasia was 1.8 % pyrs in the SSBE cohort. In contrast, another meta-analysis by Yousef et al [64] found no difference in the pooled estimate of overall cancer incidence between patients with LSBE (0.67 % pyrs) and those with SSBE (0.61 % pyrs).…”
Section: Be Length and Carcinogenesissupporting
confidence: 79%
“…There are a few reports from the West in which the lower end of the palisade vessels is used as the landmark for the EGJ as in Japan [17][18][19]. An important disadvantage of considering the proximal ends of the gastric folds as the landmark for the EGJ is that the diagnostic concordance is very low, especially in ultra-short (\1 cm in length) and short-segment BE (SSBE), in which is difficult to detect this landmark.…”
Section: Argument Regarding Landmark Of Esophagogastric Junction In Tmentioning
confidence: 99%
“…These include high-dose proton pump inhibition with surveillance, photodynamic therapy, argon-beam coagulation, laser ablation, multipolar electrocoagulation, endoscopic mucosal resection, and cryotherapy. Medical therapy with maximal acid suppression has generally shown poor rates of Barrett's metaplasia regression, and an optimal protocol for surveillance is yet to be fully validated [17][18][19]. Issues with respect to these techniques have centered around incomplete ablation, especially this issue of ''buried glands'' (i.e., Barrett's metaplasia persistent under of layer of normal squamous epithelium) [8][9][10][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopically, this is accepted as the most proximal level of gastric folds whereas the squamocolumnar junction is the border between esophageal squamous mucosa and gastric columnar mucosa. Specialized intestinal metaplasia in the short segment of Barrett's esophagus (SSBE) has been reported to revert with medication, whereas the progression to carcinoma is signifi cantly high in long segments of Barrett's esophagus (LSBE) Duration of procedure is in minutes NG, not given; MBDB, methylene blue-directed biopsies; RB, random biopsies [32,33]. It has been suggested that the LSBE requires more frequent surveillance assessments.…”
Section: Discussionmentioning
confidence: 99%